SHOULD WE ABOLISH THE DELICT OF SEDUCTION IN CUSTOMARY LAW: QUO VADIS SOUTH AFRICA? - Nqobizwe Mvelo Ngema; WJ Ndaba (Obiter, 2022)
This note investigates whether or not the time is ripe for South Africa to abolish the delict of seduction. The legislature has not yet abolished the delict of seduction in customary law. In addition, there are a growing number of academic commentators who are in full support of Bohler-Muller’s recommendation for the abolition of the delict of seduction in customary law. In investigating whether it is ripe for South Africa to abolish the delict of seduction under customary law, the first part of the note discusses the existing problems in customary law governing the delict of seduction. The second part discusses four challenges that might be created by its abolition under the following sub-topics, namely (a) social advantages for prohibiting pre-marital sexual intercourse; (b) religious consequences of pre-marital sexual intercourse and advantages for discouraging pre-marital sexual intercourse; (c) the link between the delict of seduction under customary law and the payment of lobolo; and (d) the relationship between the customary law delict of seduction and the value of gender equality. The third part of the note discusses the possible solutions to the problems.